ANALISIS SISTEM ANTRIAN PELAYANAN DI BANK JATENG KANTOR UNIVET DENGAN METODE WIN QS - Darsini; Mathilda Sri Lestari; Suprapto (INKOFAR, 2025)
Queueing problems at service facilities often lead to long waiting times during peak hours. At the Bank Jateng service counter located at Univet, which serves both students and surrounding residents, queue congestion frequently occurs at the beginning of the month and during certain service hours. This study aims to analyze the queueing system at the Bank Jateng Univet Office using a single-channel, single-phase (M/M/1) queueing model. The analysis was conducted using WinQSB software based on primary data collected through direct observation during operational hours and interviews with bank staff. The results show that the average customer arrival rate (λ) was 23 customers per hour, while the service rate (μ) was 26 customers per hour. The average number of customers in the system (Ls) was 11 people, with an average queue length (Lq) of 10 people. The average time spent in the system (Ws) was 0.5 hours. The service facility utilization rate (ρ) reached 88.46%, indicating a high workload level. Although the system operates under stable conditions, service capacity improvements are recommended to reduce waiting times during peak periods.